The Effect Of Profitability, Investment Decisions And Corporate Social Responsibility On Company Value In Healthcare Companies Listed On The Idx From 2018-2022 - Nurul Fahira; Patar Marbun; Ahmad Prayudi; M. Yamin Siregar (International Journal of Economic Research and Financial Accounting, 2024)
This study aimed to determine “The Effect of Profitability, Investment Decisions and Corporate Social Responsibility on Company Value in Healthcare Companies Listed on the IDX from 2018-2022”. This is the result of quantitative research study. The sample in this study consisted of 30 data points collected using the companies' annual reports. The sampling technique used was purposive sampling with the significance level of 0.05. Based on the results, Profitability (ROA) has a positive and significant effect on Company Value (PBV), Investment Decisions (PER) has a positive and significant effect on Company Value (PBV), Corporate Social Responsibility (CSRDI based on GRI indicators) has a positive and significant effect on Company Value (PBV), Profitability, Investment Decisions and Corporate Social Responsibility simultaneously had a positve and significant effect on Company Value in Healthcare Companies Listed on the IDX From 2018-2022.